+0  
 
0
110
1
avatar+55 

help

1)

2)

 Oct 18, 2018
 #1
avatar+98090 
+1

x / 2  -   2 / [ x + 1 ]   =   1       get a common denominator on the left

 

  [ x [ x + 1 ]   - 2*2 ) / [ 2 ( x + 1) ]  =  1

 

[ x^2 + x - 4] / [ 2x + 2 ]  =1      multiply both sides by  2x + 2

 

x^2 + x  - 4 =  2x + 2      subtract  2x, 2 from both sides

 

x^2 - x - 6  =  0     factor

 

(x - 3) ( x + 2)  = 0      

 

Set both factors to 0 and solve for x   and we get that

 

x = 3   or  x =  -2

 

 

 

8 ( x + 3)^2            8      ( x + 3)^2

__________     =  _    * _______   =     4 (x + 3)  =   4x + 12

2  ( x + 3)              2       ( x + 3)

 

 

 

cool cool cool

 Oct 18, 2018

24 Online Users

avatar
avatar
avatar
avatar